2010
DOI: 10.1128/aac.00353-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tuberculosis, Race, and Human Gene SLCO1B1 Polymorphisms on Rifampin Concentrations

Abstract: Rifampin has concentration-dependent activity against Mycobacterium tuberculosis. However, marked intersubject variation of rifampin concentrations occurs. In this study, we evaluated rifampin pharmacokinetics in relation to tuberculosis, geographic region, race, and single nucleotide polymorphisms of the human transporter genes SLCO1B1, SLCO1B3, and MDR1. Seventy-two adults with pulmonary tuberculosis from Africa, North America, and Spain were evaluated during multidrug intensive-phase therapy, and their resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 28 publications
(32 reference statements)
7
128
7
Order By: Relevance
“…Surprisingly, SLCO1B1 genotypes were not found to affect drug exposure in our study population. These results are in contrast to those reported by Weiner et al and Chigutsa et al, who have reported that SLCO1B1 rs4149032 was associated with substantially reduced rifampin exposure (37,38). However, our results are in line with those from a Chinese study (39).…”
Section: Discussioncontrasting
confidence: 58%
“…Surprisingly, SLCO1B1 genotypes were not found to affect drug exposure in our study population. These results are in contrast to those reported by Weiner et al and Chigutsa et al, who have reported that SLCO1B1 rs4149032 was associated with substantially reduced rifampin exposure (37,38). However, our results are in line with those from a Chinese study (39).…”
Section: Discussioncontrasting
confidence: 58%
“…An association has been reported between an SLCO1B1 polymorphism and rifampin PK (20,21). It is important to consider whether these polymorphisms affect drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms reported to predict plasma PK of efavirenz (11)(12)(13)(14)(15), rifampin (20,21), and lopinavir (17,18) were genotyped in duplicate. For efavirenz, CYP2B6 516 G¡T (rs3745274), 983 T¡C (rs28399499), and 15582 C¡T (rs4803419) were assayed using MassARRAY iPLEX Gold (Sequenom Inc., San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…3 Despite this concern, there is limited RIF dosing information to ensure optimal outcome. A number of studies have shown interindividual RIF pharmacokinetic variability [4][5][6] and this genetic diversity may support the need to increase RIF dosage in Indonesian TB patients. 7 Recent research has explored a link between genetics and treatment efficacy 4,8 and the present study is the first to assess genetic diversity in Indonesian patients with confirmed diagnosis of pulmonary TB (PTB) and extrapulmonary TB (EPTB).…”
Section: 2mentioning
confidence: 99%